Pressão do tempo e informações adicionais no processo decisório: um estudo de abordagem experimental - Sincorá, Larissa Alves (2022)
This thesis aims at understanding whether there is any difference in the influence of time pressure and additional informations in the decision-making process of more cognitive reflective individuals (analytical) related to less cognitive reflective ones (impulsive). In order to do so, it was combined the theoretical contents that mention the decision-making process, its influential factors – time pressure and additional information with the role of financial instruction -, as well as the performance of the decision-making process. The structuring of the underlying theories included in the theoretical framework is presented from a discussion of their concepts, characteristics, and applicability, through studies that stand out in the area. In this context, one sought to critically discuss the decision-making models’ evolution within applied social sciences, in order to establish propositions to understanding the current decision-making process reality, aiming at creating contributions to the Decision-Making field of research. Based on those propositions, it was performed an experimental research (FIELD; HOLE, 2003), including two different perspectives of analysis, that is, Study 1, which investigated behavioral aspects of the phenomenon, and Study 2, which investigated cognitive aspects of the phenomenon. Study 1 involved designing a 2x2 factorial, that aimed at measuring the effects of time pressure and additional information relative influence on the decision-making performance of the individuals with different cognitive profiles. In order to do that, it was built the following theoretical propositions: more reflective individuals and less reflective individuals are affected in different ways by time pressure and additional information in the decision-making process (H1); more cognitive reflective individuals, when affected by time pressure, tend to have a better decision-making performance when compared to less cognitive reflective individuals (H1a); more cognitive reflective individuals, when presented to additional information, tend to have a better decision-making performance when compared to less cognitive reflective individuals (H1b) and; more cognitive reflective individuals, when simultaneously affected by time pressure and in the presence of additional information, tend to the a better decision-making performance when compared to less cognitive reflective individuals (H1c). On the other hand, Study 2 presented a 2x1 factorial design, which measured the effects of time pressure relative influence, specifically on the cognition of individuals categorized as more or less reflective. Therefore, two theoretical hypotheses were drawn: initial responses that are followed by a low FOR (Feeling of Rightness) are associated to more analytical engagement (Type 2 thoughts), than the responses associated to a high FOR (H2), and; more reflective thinkers are better in monitoring and controlling reasoning than less reflective ones (H3). Thus, methodologically, this research involved a non-probabilistic sample, with 521 undergraduate students of an Education Institution located in the state of Espirito Santo (covering all courses, shifts, semesters and campi of the institution), collected through the convenience criteria (COZBY, 2003). As a result, it was identified that more reflective individuals, when pressured by time restriction and in presence of additional informations of financial instructions, demonstrate a higher (better) decision-making performance (confirming H1, H1a, H1b and H1c); besides experiencing more decision-making certainty (FOR) during their processes of judgement and decision making, than their counterpart, less reflective (confirming H3). However, the same metacognitive feeling (FOR) was not capable of predicting more analytical engagement of the individuals in their decision-making processes, whether they are more or less reflective (rejecting H2). Those respective findings may be directly explained by the level of cognitive reflexivity shown by the investigated subjects, that is, when categorized in terms of being more reflective (analytical) or less reflective (impulsive), representing an explanatory mechanism to the differences between the performances. Therefore, by meeting the proposed objectives, as well as the results evidenced with the theoretical propositions’ test, it was possible to sustain the main argument defended in this thesis, which is based on the statement that “The pressure put on the individual by time restriction, as well as the presence of additional information available at the time of the decision-making process, influences in different ways the performance of individuals categorized as more reflective related to less reflective ones.”